N. Hawthorne's The Scarlet Letter The Trial of Religion - EL-Naggar, Nehal (Advances in Social Sciences Research Journal, 2017)
The trial of religion is a controversial field of research, where questions pertaining to the re-thinking of rigid pseudo-religious dogmas should be addressed and re-examined to fit the modern age and account suitable to match the real life of man on earth with all its changes and advances. Literatures across cultures and across languages along with different ethnic groups have tackled such question with concern; sometimes blatantly and at others subtly. The trial of religion is not directed at condemning any faith or creed but a criticism of dogmatic beliefs that are never part of any religion, but are man-made to exercise power over, manipulate and control people under the umbrella of the sacredness of religion. Needless to say, this is what our age is witnessing nowadays. Everyday, religion is used to destroy peoples and nations with the pretext that we are executing the word of God. Usually, the issue of societal justice emanates from religion. In literature and in the fine arts the implementation of justice is at many times represented through a trial or scaffold scene. World culture abounds in famous trial scenes that had a great impact on literature and that bear witness to the practice of justice or actually ‘injustice’. The most well-known are those of Socrates and Christ. In fiction such topic has been at many times represented also in an actual scaffold scene or through a metaphoric one. For instance, Nathaniel Hawthorne's (1804-1864) The Scarlet Letter (SL) (1850). In it the trial of religion is there for the readers to consider and deliberate. It is an attempt to re-think rigid religious dogmas. Nathaniel Hawthorne's (1804-1864) The Scarlet Letter (1850) is a good illustration of the trial of religion. It is the trial of rigid religious dogmas and beliefs. This study proposes to consider the scaffold scenes in The Scarlet Letter in a way to measure their centrality or importance in the text; how they are presented, dealt with and resolved. It will present the ideas that this kind of trial is unfolding to be a pointer to larger issues that are applicable in our modern times. The cultural context is of ultimate importance as it allows the reader to reach out for more universal issues that are pertinent to all times. The Scarlet Letter studies the story of three sinners and the consequences of their acts, which led them to be tried literally, psychologically and metaphorically. The trial is a direct critique of rigid religious understanding. It is the trial of religion by large. What is needed is a different way to think in order to make a change in society. This will challenge the dominant or the accepted social beliefs that have their roots in religion. It offers and visualizes another way to understand and thus to live. This study provides a different context within which we have to face the proliferation of texts that propagate rigid ideologies.